Guillermo del Toro's Insane. - Shaw, Patrick
We examine the acclaimed filmmaker's expect from his horror-game trilogy.
Keywords: Toro, Guillermo del, 1964-.; Blade II (Motion picture); Hellboy (Motion picture); Horror films